Enhanced Electrocatalytic Oxidation of Formic Acid on Au(111) in the Presence of Pyridine. Issue 15 (6th October 2018) - Hermann, Johannes M.; Mattausch, Yannick; Weiß, Annchristin; Jacob, Timo; Kibler, Ludwig A.
Abstract : The adsorption of pyridine on Au(111) single crystal electrodes has been systematically studied in a broad range of pH values between 1 and 13. From the voltammetric features of Au(111) in 0.1 M pyridine a potential/pH diagram has been derived, which classifies various phases for adsorbed pyridine. At sufficiently high concentrations of unprotonated pyridine in solution, a significantly enhanced activity for formic acid oxidation on Au(111) is observed in a narrow potential region, where strongly bound formate has not yet reached its saturation coverage. The various pyridine structures exhibit different enhancement factors. At positive potentials, the typical features of formic acid oxidation on Au(111) are present, pointing toward complete replacement of adsorbed pyridine by formate.